2018
DOI: 10.1186/s12936-017-2144-x
|View full text |Cite
|
Sign up to set email alerts
|

In silico epitope mapping and experimental evaluation of the Merozoite Adhesive Erythrocytic Binding Protein (MAEBL) as a malaria vaccine candidate

Abstract: BackgroundTechnical limitations for culturing the human malaria parasite Plasmodium vivax have impaired the discovery of vaccine candidates, challenging the malaria eradication agenda. The immunogenicity of the M2 domain of the Merozoite Adhesive Erythrocytic Binding Protein (MAEBL) antigen cloned from the Plasmodium yoelii murine parasite, has been previously demonstrated.ResultsDetailed epitope mapping of MAEBL through immunoinformatics identified several MHCI, MHCII and B cell epitopes throughout the peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…However, a better understanding of the interactions between the ZIKV and DENV immunity, such as induction by vaccination or by natural infection, will be necessary to provide safe and efficient vaccines [115]. Several studies have reported how the computational prediction of antigenic peptides were successfully validated experimentally to combat HIV-1, malaria parasites and leishmaniasis, a vector-borne parasitic disease [116,117,118]. In validating the predicted epitopes, it is suggested to integrate genomics with proteomics approaches to represent a valid strategy in refining the antigen characterizations as well as give the useful insights on abundance and subcellular localization of pathogenic antigens [119].…”
Section: Discussionmentioning
confidence: 99%
“…However, a better understanding of the interactions between the ZIKV and DENV immunity, such as induction by vaccination or by natural infection, will be necessary to provide safe and efficient vaccines [115]. Several studies have reported how the computational prediction of antigenic peptides were successfully validated experimentally to combat HIV-1, malaria parasites and leishmaniasis, a vector-borne parasitic disease [116,117,118]. In validating the predicted epitopes, it is suggested to integrate genomics with proteomics approaches to represent a valid strategy in refining the antigen characterizations as well as give the useful insights on abundance and subcellular localization of pathogenic antigens [119].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these GPI-anchored surface proteins were screened as malarial adhesins and adhesin-like proteins by MAAP tool [ 24 26 ]. The VaxiJen2.0 program was used for the evaluation of antigenicity of the malarial adhesins protein sequence [ 27 , 28 ]. Furthermore, to assess the potential impact of membrane proximity, transmembrane regions of potential antigens (pathogenesis-related secretome of P. falciparum ) were predicted using TMHMM2.0 tool [ 29 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…MAEBL is a membrane protein of the erythrocyte binding protein (EBL) family. It is expressed in preerythrocytes, blood stage, and salivary glands ( 31 ). Immunoinformatic analysis showed that MAEBL antigens could be promising interspecies and inter strain malaria candidates since they have several conserved epitopes among P. yoelli , P. falciparum and P. vivax ( 31 ).…”
Section: Multistage Vaccinementioning
confidence: 99%
“…It is expressed in preerythrocytes, blood stage, and salivary glands ( 31 ). Immunoinformatic analysis showed that MAEBL antigens could be promising interspecies and inter strain malaria candidates since they have several conserved epitopes among P. yoelli , P. falciparum and P. vivax ( 31 ). Functional studies showed that antibodies against PyMAEBL-M2 were reactive against P. falciparum and P. vivax with significant inhibition of erythrocyte invasion of these parasites ( 31 ).…”
Section: Multistage Vaccinementioning
confidence: 99%
See 1 more Smart Citation